Res Ipsa Loquitur: Evidence in Civil Law and Islamic Law; Viewed from a doctrinal point of view - windy virdinia putri; Muchammad Ichsan; Nanik Prasetyoningsih (Faculty of Law, Universitas Pekalongan, 2023)
In cases of suspected medical malpractice, it is tough to prove that there is an element of negligence because access to evidence is within or under the perpetrator's control, making it difficult for the victim to access it. In the legal field, the doctrine of res ipsa loquitur was introduced, which makes it easier for victims to prove who is guilty by showing indirect evidence, namely evidence of a fact or several facts from which a reasonable conclusion can be drawn. This research examines the application of res ipsa loquitur in terms of doctrine, civil evidence law, and Islamic law. This research is a literature study using a normative approach that refers to civil evidence law and Islamic law provisions. The legal analysis used is a conceptual, comparative and case study approach. This research found that applying res ipsa loquitur in judicial practice, as long as it is not regulated in procedural law, is a principle that becomes a source for judges to find the law. In civil evidence law, res ipsa loquitur can be implemented through presumptive evidence concluded by the judge. Meanwhile, in Islamic law, there are dalil (instructions) for qarinah, which are equated with presumptive evidence, so that res ipsa loquitur, which can be enforced through presumptive evidence, can also be enforced through qarinah evidence.